Rural Finance Policies 14 - The scope for policy reforms in rural microfinance - Sharma, Manohar (International Food Policy Research Institute, 2000)
This brief considers the scope for policy action in seven areas: (1) regulation of microfinance institutions, (2) provision of saving services, (3) product innovation, (4) organizational issues in microfinance, (5) poverty impact of microfinance, (6) agricultural finance, and (7) subsidy and sustainability issues.